Poe and the visual arts - Cantalupo, Barbara (The Pennsylvania State University Press, 2014)
"Explores visual allusions in the writings of Edgar Allan Poe to paintings and sculptures he saw in Philadelphia and Manhattan. Examines how his writings relate to the visual culture of his time"--Provided by publisher